Pemanfaatan Asap Cair Hasil Pirolisis Batubara sebagai Pestisida Organik pada Rayap (Coptotermes curvignathus Holmgren) - Arman, Muh; Bakri, Suriyanto; Majid, Rafdi Abdul (Jurnal Teknik Kimia USU, 2021)
Pyrolysis is a process of chemical decomposition of materials through a heating method in the absence of oxygen or a little oxygen. The utilizing coal as a raw material for making liquid smoke, it is hoped that it will be able to produce pesticides that have economic value and can be used as a termite exterminator. The use of coal as a raw material for making liquid smoke is expected to produce pesticides that have economic value and can be used as a termite repellent. This research aimed to determine the optimum concentration and time of liquid coal smoke as a pesticide against termite insect mortality (Coptotermes curvignathus Holmgren). The method used is the coal pyrolysis process at a temperature of 300 0C. The process of testing the mortality of termites with time and concentration variables. The determination of the liquid smoke content of coal is carried out by qualitative and quantitative analysis. The results showed that the optimum time for termite mortality was 25 minutes with an optimum concentration of 80%, where the termite mortality was obtained by 100%. Based on the results of UV/VIS Spectrophotometer Analysis, the sulfur content of liquid coal smoke was 46.92 mg/kg, and the degree of acidity (pH) was 3.00. The acidity content is high enough to allow pesticides from liquid coal smoke to be widely used in agriculture.